Enhancing student employability skills through virtual field trips in the hospitality industry : final report. - Patiar, Anoop; Benckendorff, Pierre; Kensbock, Sandie; Wang, Ying; Wilkins, Hugh; Robinson, Richard; Richardson, Scott; Lee, Andy; Goh, Edmund (Australia. Dept of Education and Training (DET), 2019)
Hospitality fieldwork offers student-centred experiential learning and an opportunity to establish authentic connections between theory and practice. Ongoing reductions in the funding of universities and increasing student numbers have led to technology-enhanced solutions to provide practice-based learning experiences in hospitality management education. Virtual field trips (VFTs) are an alternative and flexible means for students to connect their classroom learning with authentic activities and assessment via structured experiences in participating hospitality businesses. In 2013, Griffith University provided seed funding to develop and trial VFTs of two hotels in Queensland. The VFTs were implemented in a core course within the Bachelor of International Tourism and Hotel Management. The course content and assessment were integrated and constructively aligned with the VFTs (Biggs, 2003) and evaluated for effectiveness using mixed methodologies. Students found the VFTs to be highly effective in reinforcing the course content and adding to their learning experience. They also found the VFTs to be relevant and useful in informing their assessment tasks. [Executive summary, ed]